2013
DOI: 10.3901/cjme.2013.01.207
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of oil consumption in cylinder of diesel engine for optimization of piston rings

Abstract: The performance and particulate emission of a diesel engine are affected by the consumption of lubricating oil. Most studies on oil consumption mechanism of the cylinder have been done by using the experimental method, however they are very costly. Therefore, it is very necessary to study oil consumption mechanism of the cylinder and obtain the accurate results by the calculation method. Firstly, four main modes of lubricating oil consumption in cylinder are analyzed and then the oil consumption rate under com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…This may lead to an increased rate of oil evaporation from the cylinder liner during the expansion stroke, which is when most of the oil evaporates from the engine. 36,37 Finally, we also conclude that potential biological effects of lubrication oil components should be investigated in closer detail (e.g., in air−liquid−interface exposure experiments 29 ).…”
Section: Emission Factors Of Lubricant Oil Hydrocarbons the Wide Rang...mentioning
confidence: 68%
See 1 more Smart Citation
“…This may lead to an increased rate of oil evaporation from the cylinder liner during the expansion stroke, which is when most of the oil evaporates from the engine. 36,37 Finally, we also conclude that potential biological effects of lubrication oil components should be investigated in closer detail (e.g., in air−liquid−interface exposure experiments 29 ).…”
Section: Emission Factors Of Lubricant Oil Hydrocarbons the Wide Rang...mentioning
confidence: 68%
“…Stengel et al recently observed on the same engine that MGO ignites before the top dead center of the piston, while HFO ignites only after the top dead center. This may lead to an increased rate of oil evaporation from the cylinder liner during the expansion stroke, which is when most of the oil evaporates from the engine. , …”
Section: Discussionmentioning
confidence: 99%
“…Since particulate emissions in diesel engines are dominated by unburnt fuel emissions (e.g. soot), research is more focussed on fuel-oil interaction and lube oil consumption rather than oil emissions, as seen in Zhang et al, 14 Pasligh et al 15 Due to the mechanisms being related, findings also show the above-mentioned necessity to co-develop piston rings and cylinder liners.…”
Section: Oil Emissionsmentioning
confidence: 99%